Dual Role of MSC-Derived Exosomes in Tumor Development - Rou Zhao; Xinke Chen; Hui Song; Qingli Bie; Bin Zhang (Stem Cells International)
Mesenchymal stem cells (MSCs) are a class of adult stem cells derived from the mesoderm. They can self-renew, have multidirectional differentiation potential, and can differentiate into a variety of mesenchymal tissues. MSCs can produce a large number of exosomes, which can mediate information exchange and transmission between cells in the tumor microenvironment under conditions of rest or stress. Recent studies have reported conflicting findings regarding the effect of MSC-derived exosomes on tumors. Some studies have suggested that MSC-derived exosomes can promote tumor growth and metastasis, but others have reported that they can inhibit tumor cell growth. Here, we investigate the two sides of the debate regarding the effect of MSC-derived exosomes on tumors and analyze the reasons for the divergent findings.